Proceedings of the 1995 Academy of Marketing Science (AMS) Annual Conference - Gomes, Roger; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume includes the full proceedings from the 1995 Academy of Marketing Science (AMS) Annual Conference held in Orlando, Florida. The research and presentations offered in this volume cover many aspects of marketing science including marketing strategy, consumer behavior, advertising, branding, international marketing, marketing education, among others. Founded in 1971, the Academy of Marketing Science is an international organization dedicated to promoting timely explorations of phenomena related to the science of marketing in theory, research, and practice. Among its services to members and the community at large, the Academy offers conferences, congresses and symposia that attract delegates from around the world. Presentations from these events are published in this Proceedings series, which offers a comprehensive archive of volumes reflecting the evolution of the field. Volumes deliver cutting-edge research and insights, complimenting the Academy’s flagship journals, Journal of the Academy of Marketing Science (JAMS) and AMS Review. Volumes are edited by leading scholars and practitioners across a wide range of subject areas in marketing science.
High Technology and Computers in the Global Environment -- Advertising: Images and Differential Effects -- Pricing and Product/Brand Mangement -- Buyer Behavior and Consumer Issues -- Macromarketing and Public Policy -- Similarity, Schematicity, and Choice Clustering in Consumer Behavior -- The Marketing Concept Revisited -- Exploring Consumption Behavior Differences and Asymmetries Between Groups -- Retail Patronage and Perceived Value Across Cultures -- Strategy, Strategic Orientation, and Strategic Response -- Global Marketing Strategy -- Sales Motivation and Compensation -- Selling and Sale Management -- Free Trade and International Marketing Strategy -- Conceptual & Modeling Issues in Services Marketing -- Quantitative Methods -- Country-of-Origin and Ethnocentrism -- Emerging Issues in Professional Services Marketing -- Elements of Channel Relationships -- Positioning in Channel Relationships -- Advances in Research on Marketing of Industrial Services -- Non-Quantitative Methods -- Macromarketing in the Global Environment -- Inventory, Price and Sales Management in the Retailing Environment -- Research Areas in Channel Relationships -- Market Entry and Internationalization -- Strategic Options and Related Organizational Issues -- Marketing Education Issues.
Keywords: Marketing; Leadership; Sales management; Marketing; Business Strategy/Leadership.; Sales/Distribution.